Babies by design : the ethics of genetic choice - Green, Ronald Michael (Yale University Press, 2007)
Product Description: We stand on the brink of unprecedented growth in our ability to understand and change the human genome. New reproductive technologies now enable parents to select some genetic traits for their children, and soon it will be possible to begin to shape ourselves as a species. Despite the loud cries of alarm that such a prospect inspires, Ronald Green argues that we will, and we should, undertake the direction of our own evolution. A leader in the bioethics community, Green offers a scientifically and ethically informed view of human genetic self-modification and the possibilities it opens up for a better future. Fears of a terrible Brave New World or a new eugenics movement are overblown, he maintains, and in the more likely future, genetic modifications may improve parents' ability to enhance children's lives and may even promote social justice. The author outlines the new capabilities of genomic science, addresses urgent questions of safety that genetic interventions pose, and explores questions of parenting and justice. He also examines the religious implications of gene modification. Babies by design are assuredly in the future, Green concludes, and by making responsible choices as we enter that future, we can incorporate gene technology in a new age of human adventure.